2016
DOI: 10.1002/eqe.2785
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of a tall metal wind turbine support tower with realistic geometric imperfections

Abstract: analysis of a tall metal wind turbine support tower with realistic geometric imperfections. Earthquake Engineering and Structural Dynamics, 46(2), pp. 201-219. doi: 10.1002/eqe.2785 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThe global growth in wind energy suggests that wind farms will increasingly be deployed in seismically active regions, with large arrays of similarly-designed structures potentially at risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…In near‐fault regions, ground motions have long been known to inherit velocity pulses of large amplitude, being distinctly different from far‐field ground motions . In case of a 1.5MW onshore wind turbine, Sadowski et al showed near‐fault records with pulse‐like effects more damaging than far‐field records. Near‐fault pulses are produced because of either forward propagation of the fault rupture towards the site, i.e., directivity effects, or fault displacement due to rupture, known as fling‐step effects .…”
Section: Introductionmentioning
confidence: 99%
“…In near‐fault regions, ground motions have long been known to inherit velocity pulses of large amplitude, being distinctly different from far‐field ground motions . In case of a 1.5MW onshore wind turbine, Sadowski et al showed near‐fault records with pulse‐like effects more damaging than far‐field records. Near‐fault pulses are produced because of either forward propagation of the fault rupture towards the site, i.e., directivity effects, or fault displacement due to rupture, known as fling‐step effects .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Penzien et al [11] recommended that proper plastic response should be considered in the seismic analysis of offshore structures. Therefore, Kim et al [12], Nuta et al [13], and Sadowski et al [14] investigated the inelastic response of OWTs under seismic loads. Kim [11] performed the seismic fragility analysis of OWTs considering the non-linear effects of soil-pile interaction and suggested that the applied ground motion should be calculated for each soil layer to obtain equitable fragility curves of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nuta et al [13] investigated the probability of damage in tubular steel towers at varying seismic hazard levels, defined the fragility curves of the towers by considering different damage states in the analysis, and proved that large safety factors must be considered in the design against the phenomenon of overloading under seismic loads. Sadowski et al [14] researched the responses of the tower under seismic loads with respect to geometric imperfections and discussed the influence of the imperfections on the capacity of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in Greek antiseismic specifications, the elastic acceleration reaction spectrum in near‐field zones requires further improvement. Sadowski et al investigated the dynamic response pattern of a wind turbine tower with a cylinder with an initial defect subjected to near‐field and far‐field ground motion. For the near‐field pulse ground motion, the tower damage was much more severe than the damage from far‐field ground motion.…”
Section: Introductionmentioning
confidence: 99%